Isolation and Identification of Soil Fungi from Mangrove In Nakhon Si Thammarat Province - เลี่ยมทอง, สุมาลี (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2017)
The aim of this study was to isolate and identify soil fungi in mangrove areas in Muang, Pakpanang and Thasala Districts, Nakhon Si Thammarat Province. The morphological study of fungi showed that from the total of 161 isolates, 124 isolates (77.0%) produce spores and can be classified. Penicillium spp. were found to be the most dominant fungi (52 isolates; 32.3%) followed by Aspergillus spp. (43 isolates; 26.7%), Trichoderma spp. (19 isolates; 11.8%), Fusarium spp. (6 isolates; 3.7%), Drechslera spp. (2 isolates; 1.2%), Gongronella sp. (1 isolate; 0.6%) and Dendryphiopsis sp. (1 isolate; 0.6%). Thirty-six isolates (22.4%) did not sporulate being classified as mycelia sterilia while one isolate (0.6%) produced spore but cannot be classified. The results of this study revealed the types of fungi isolated from mangrove soil. This information can be used to support further studies in term of fungal activities.